Assessment of drilling characteristics of alumina coated on aluminium using CO2 laser. (March 2017) - Bharatish, A.; Narasimha Murthy, H.N.; Anand, B.; Subramanya, K.N.; Krishna, M.; Srihari, P.V.
Highlights: Spatter deposition due to laser drilling was analysed. Simultaneous optimisation using Genetic Algorithm. Plasma spraying of alumina on aluminium. Abstract: This paper reports experimental investigation of effect of laser parameters on the drilling responses of alumina coated aluminium substrates using 1.8 kW CO2 pulsed mode laser. Alumina was deposited on 4 mm thick Al 6065 plates by plasma spray technique. The main influencing factors were: Laser power on spatter deposition and Heat Affected Zone; Pulse frequency on entrance and exit circularities; Piercing time on taper, heat affected zone and exit circularity. Genetic algorithm optimization results indicated simultaneous improvement of 5.2% in hole quality at 416.6 W laser power, 1.4 kHz pulse frequency and 0.4 s piercing time. Response Surface Methodology indicated minimum spatter deposition area of 11.57 mm 2, Heat Affected Zone 0.589 mm, taper 2.35° and maximum circularity at entrance 0.88 and exit 0.905 at 400 W laser power, 1.2 kHz frequency and 0.48 s piercing time. These results were in close agreement with those of Genetic algorithm. The optimum values were validated through confirmatory experiments.